Distribution and fate of 14C-carbofuran in model rice-fish ecosystem - R. B., Mohamad; H. A., Juzu; A. R., Ismail (1988)
Distribution, metabolism and persistence of 14C-carbofuran in model rice-fish ecosystem was studied using nuclear technique. Carbofuran, when applied to the water disappeared within a short period. About 80% of the total carbofuran applied was loss within 14 days after the' application. Correspondingly, an increase of about 70% of the total application was recorded in thes soil within. 21 days, with higher concentration in the upper 5 cm layer. Most residues in the soil remained bound to the soil particles, which increased over time. Extractable residues depleted with time.Build up of absorbed residues in the plant was slow, reaching maximum level of 28% of the total applied carbofumn after 28 days. In the plant, active transport to and accumulation in the aerial parts occured during the early growth period (about 28 days after transplanting), but later the chemical was accumulating in the root. Some residues were also detectable in the rice grains. Perch fish cannot willlstand direct application of carbofuran inlo the water. All the fish died wilhin 24h. Toxic metnbolilcs of 3-kelO and/or 3-hydrox)' carbofuran were detectable in the water. Only carbofuran phenol and 3-hydroxy carbofuran were found in the soil and paddy plant, respectively.